The Impact of Culture, Environment, Discipline, and Job Satisfaction on Employee Performance at PT Pegadaian Surabaya - Nizar, Nizar Zakaria; Saptaria, Lina (Jurnal Penelitian Ekonomi Dan Akuntansi, 2024)
This study aims to determine the influence of work culture, work environment, work discipline, and job satisfaction on employee performance using the Resource-Based View theory approach. The design of this study is quantitative associative. The population of this study were employees of PT Pegadaian, Regional Office XII Surabaya. With the aid of the Smart PLS 3.0 application, the data analysis method employed the Structural Equation Model (SEM) PLS (Partial Least Square) approach. The results of the data analysis show that: (1) Work culture has a positive and significant effect on work discipline . (2) The work environment has a positive and significant effect on job satisfaction . (3) Work discipline has a positive and significant effect on job satisfaction . ( 4 ) Job satisfaction has a positive and significant effect on employee performance . ( 5 ) Work culture does not influence job satisfaction through work discipline as an intervening variable . ( 6 ) Work discipline influences performance through job satisfaction as an intervening variable . ( 7 ) The work environment influences employee performance through job satisfaction as an intervening variable . ( 8 ) Work culture influences employee performance through work discipline and job satisfaction as intervening variables . The implication of this research is that companies can identify important organizational resources, namely work discipline, work environment, work culture and understand the relationship between resources to create optimal performance improvement strategies